Furosemide Diuretic Activity Evaluation in Female Sprague-Dawley Rats - Castillo Henríquez, Luis (2019)
This research article focuses on the evaluation of the diuretic activity of Furosemide administered to a group of female Sprague Dawley rats, through the use of metabolic boxes. Methods: A hydration volume of 5 mL/100 g was administered by cannulas for oral administration to group I (Furosemide) and to group II (control). After 2 h the basal urine volume was determined. Group I was given 20 mg/kg of Furosemide and group II 20 mg/kg of physiological saline solution, both intraperitoneally. After the administration of the new hydration load of 5 mL/100 g, the measurements of excreted urine volume and its pH were done every 30 minutes for 2 h. Results: The maximum urinary excretion caused by this drug was achieved at 30 minutes post - administration, which shows a statistically difference with respect to the control group. However, after 60 minutes it is observed that the diuretic activity begins to decrease markedly due to the compensatory mechanisms of the physiology of the animal and the pharmacokinetics of the drug. Conclussion: The rapid onset of action and brief effect showed by Furosemide is consistent with what is established in the literature. Likewise, the slight decrease in post-treatment urinary pH with respect to the basal level, adjusts to the effect of Furosemide itself and to the expansion effect of the urinary volume.